Potret Netnografi Masyarakat Terhadap Video Branding Majesty Group - Sembiring, Evaliata Br; Diana, Asna (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2023)
Majesty Group is a parent company that has evolved in various business fields, especially in Batam City, and wants to build assets to be developed so that they can be known by the public. Company branding is very important, especially in today's digital age. Therefore, in this study, branding was made in the form of a Company Profile video. This study applies the R n D approach, namely making branding videos using the production stages on Villamil-Mollina and analyzing the influence of video in introducing the company with the Netnography approach. The result of the study was an increase in the percentage of public recognition of Majesty Group by 79.2%. Meanwhile, the introduction of the company based on Youtube data through the number of likes, views, and comments based on 4 features, including: Summary, Reach, Interaction and Audience, obtained an engagement rate reaching 4.0%. This indicates that the video as a company branding has a "High" value so that the resulting product has an influence in introducing the company.